Childhood vaccination practices and associated factors among mothers/caregivers in Debre Tabor town, Northwest Ethiopia: A cross-sectional study - Simegn, Wudneh; Diress, Mengistie; Gela, Yibeltal Yismaw; Belay, Daniel Gashaneh; Ayelign Kibret, Anteneh; Chilot, Dagmawi; Sinamaw, Deresse; Abdu Seid, Mohammed; Andualem, Amare Agmas; Anmut Bitew, Desalegn; Eshetu, Habitu Birhan; Mohammed Seid, Abdulwase (Frontiers in Pediatrics, 2023)
Background: Incomplete as well as non-immunization raises the risk of disease and death among children. This study aimed to assess childhood vaccination practice and associated factors among mothers/caregivers in Debre Tabor Town, Amhara region Ethiopia. Methods: A community based cross-sectional study design was conducted from February 30 to April 30, 2022. The study participants were proportionally allocated to all six kebeles found in the town. Systematic random sampling technique was used to select the study participants. The collected data was checked, and coded then entered to Epi data version 3.1 and exported into SPSS Version 26. Results were organized using frequency tables, graphs and charts and bivariate and multivariable logistic regression was used to test the association of covariates with childhood vaccination practice. Result: About 422 study mothers/caregivers participated with a response rate of 100%. The mean age was 30.63 years (±11.74) which ranged from 18-58 years. More than half of the study participants (56.4%) fear side effects of vaccination. Majority (78.4%) of the study participants had got counseling service about vaccination; and 71.1% of participants had regular antenatal care. In the current study, about 280 (66.4%, 95% CI: 61.8, 70.6) mothers/care givers had good childhood vaccination practice. Fear of side effects (AOR=3.34; 95% CI:1.72,6.49), who has no work load (AOR=6.08; 95% CI:1.74,21.22), medium work load (AOR=4.80, 95% CI:1.57,14.71), being mother for child/children (AOR=2.55, 95% CI:1.27,5.13), positive attitude (AOR=2.25, 95% CI:1.32,3.82), and good knowledge (AOR=3.88, 95% CI: 2.26,6.68) were significantly associated with childhood vaccination practice. Conclusion: More than half of study participants had good practice of childhood vaccination. However, still it is no sufficient practice of childhood vaccination among mothers/caregivers. Fear of side effects, work load, being mother for the child/ children, attitude, and knowledge were associated factors for childhood vaccination practice. Awareness creation and considering the workload of mothers would be helpful. The authors recommend the stakeholders to design appropriate action to reduce the gaps identified and to improve childhood vaccination practice.